Residential seismic retrofitting: Contextualizing policy packages to local circumstances. (15th October 2022) - Segal, Ehud; Feitelson, Eran; Goulden, Shula; Razin, Eran; Rein-Sapir, Yonat; Kagan, Elisa Joy; Negev, Maya
Abstract: Seismic retrofitting is the most effective way to reduce casualties from earthquakes. Yet, seismic retrofitting of vulnerable residential structures faces many impediments. As no single policy measure can overcome these obstacles, seismic retrofitting requires that multiple policy measures be applied in tandem and therefore policy packages are necessary. As seismic threats are spread over multiple locales, differing in their characteristics, no single policy package is likely to fit all settings. Indeed, efforts to promote seismic retrofitting in California, New Zealand and Israel show high variability in success across different locales. Our study builds upon previous work which outlined three potential policy packages for seismic retrofitting, led by market forces, local government and central government respectively. In this study we advance an asymmetric decentralization approach to match the most appropriate policy package to local conditions. We combine this with seismic vulnerability assessment to prioritize the national allocation of retrofitting funds. The approach is applied to the Israeli case, a country that is prone to infrequent large earthquakes and in which there is a large, substandard housing stock.